2022
DOI: 10.1002/hon.3089
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1/2, open‐label, multicenter study of isatuximab in combination with cemiplimab in patients with lymphoma

Abstract: Patients with relapsed or refractory lymphoma have limited treatment options, requiring newer regimens. In this Phase 1/2 study (NCT03769181), we assessed the safety, efficacy, and pharmacokinetics of isatuximab (Isa, anti‐CD38 antibody) in combination with cemiplimab (Cemi, anti‐programmed death‐1 [PD‐1] receptor antibody; Isa + Cemi) in patients with classic Hodgkin lymphoma (cHL), diffuse large B‐cell lymphoma (DLBCL), and peripheral T‐cell lymphoma (PTCL). In Phase 1, we characterized the safety and tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…24 In this study, where renal function was even worse due to majority of patients being on dialysis, isatuximab PK exposure was comparable with those from other studies. [25][26][27] Overall, these results complement the previous analyses mentioned above, showing no effect of renal impairment on isatuximab PK exposure. These results were expected as isatuximab is a monoclonal antibody, and thus a large molecule, and is eliminated by catabolism.…”
Section: Discussionsupporting
confidence: 89%
“…24 In this study, where renal function was even worse due to majority of patients being on dialysis, isatuximab PK exposure was comparable with those from other studies. [25][26][27] Overall, these results complement the previous analyses mentioned above, showing no effect of renal impairment on isatuximab PK exposure. These results were expected as isatuximab is a monoclonal antibody, and thus a large molecule, and is eliminated by catabolism.…”
Section: Discussionsupporting
confidence: 89%
“…In the search for novel, specific target structures, the anti-CD38 mAbs Daratumumab and Isatuximab (both IgG1) are currently under investigation for the treatment of a subset of T cell lymphoma/leukemia entities [57,58]. In physiological conditions, CD38 surface expression is restricted to thymocytes, activated T cells, NK cells, and plasma cells.…”
Section: Targeting Cd38 By Daratumumab and Isatuximabmentioning
confidence: 99%
“…This study is based on the hypothesis that blocking PD-L1 on PTCL cells might restore healthy T cell mediated immune effector functions and may thus generate an additive or even synergistic immune-modulatory effect with CDC/ADCC/ADCP inducing Isatixumab. An interim analysis published at the beginning of 2023 showed a complete or partial response in only 9.1% of 11 included PTCL patients [57]. With these results, Carlo-Stella and colleagues concluded that, for PTCL patients, interim efficacy analysis results did not meet prespecified criteria to continue enrolment and that no synergistic effect could be observed.…”
Section: Targeting Cd38 By Daratumumab and Isatuximabmentioning
confidence: 99%